Work Attitudes as Correlate to Academic Performance of the Bachelor of Science in Industrial Technology Students in the University of Northern Philippines - Karlo R. Real; Joussie Bermio (Philippine Association of Institutions for Research, Inc., 2016)
The quality of student's performance in Technological Education is influenced by many factors such as facilities, equipment, hand tools, instruction, methodology, and the students. The study aimed to determine the performance of the Bachelor of Science in Industrial Technology Major in Automotive Technology students in University of Northern Philippines, Vigan City, Ilocos Sur, Philippines and the influence of some factors. The descriptive-correlational research design and documentary analysis were used. The performance was measured in terms of knowledge, manipulative skills and work attitudes. It was found out that the BSIT Program had a pool of highly qualified faculty and had more than adequate physical resources. The student respondents had fair grades in their general education subjects and good grades in technology major subjects. The level of performance of students along knowledge was good; very good along manipulative skills; and very high along work attitudes. The students' level of performance along knowledge and skills was not influenced by the BSIT program profile; however, work attitudes significantly affected the students' performance. The students' level of performance along knowledge and work attitudes was not influenced by their scholastic achievement. However, there are some aspects of skills, namely, diagnostic and speed/time which are significantly influenced by their scholastic profile.